2022
DOI: 10.3390/microorganisms10030600
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Polymorphism Survey in Intergenic Regions of the icaADBCR Locus in Staphylococcus aureus Isolates from Periprosthetic Joint Infections

Abstract: Staphylococcus aureus is a leading cause of prosthetic joint infections (PJI) characterized by bacterial biofilm formation and recalcitrance to immune-mediated clearance and antibiotics. The molecular events behind PJI infection are yet to be unraveled. In this sense, identification of polymorphisms in bacterial genomes may help to establish associations between sequence variants and the ability of S. aureus to cause PJI. Here, we report an experimental nucleotide-level survey specifically aimed at the interge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The performed experiments indicate that the role of the icaR gene in inhibiting biofilm formation is also important. As reported in the work of Morales-Laverde et al, nucleotide polymorphism in the icaR coding region leads to an increase in icaADBC transcription and PIA production [ 31 ]. Similar results were reported by Wang et al, who demonstrated an increase in the expression of the icaR gene and a decrease in the expression of the icaA gene with the use of silver nanoparticles [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The performed experiments indicate that the role of the icaR gene in inhibiting biofilm formation is also important. As reported in the work of Morales-Laverde et al, nucleotide polymorphism in the icaR coding region leads to an increase in icaADBC transcription and PIA production [ 31 ]. Similar results were reported by Wang et al, who demonstrated an increase in the expression of the icaR gene and a decrease in the expression of the icaA gene with the use of silver nanoparticles [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of S. aureus , SNPs accumulation in the IGRs of adhesin-encoding genes present in strains isolated from later points of infection has been described [ 48 ]. On the contrary, regarding the production of the main exopolysaccharide of the S. aureus biofilm matrix, SNPs in the highly conserved IGRs of the icaADBCR operon were not associated with changes in icaADBC expression, PIA/PNAG production and adaptation to PJI [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The forty-five PJI S. aureus strains were previously isolated at Sahlgrenska Hospital (Sweden) from PJI of the hip or knee [ 27 , 28 ]. Twenty-six strains from wound infections, isolated between 1966 and 2010, were obtained from the Culture Collection University of Gothenburg (CCUG) [ 29 , 30 ]. Escherichia coli and S. aureus were grown in Luria-Bertani medium (LB; Conda-Pronadisa, Madrid, Spain) and Trypticase soy broth (TSB; Conda-Pronadisa, Madrid, Spain) at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…were obtained from the Culture Collection University of Gothenburg (CCUG)(Morales-Laverde et al, 2022;Turner et al, 2022). Escherichia coli and S. aureus strains were routinely grown in Luria-Bertani medium (LB; Conda-Pronadisa, Madrid, Spain) and Trypticase soy broth (TSB; Conda-Pronadisa, Madrid, Spain), respectively, at 37°C.…”
mentioning
confidence: 99%